A study on the relationship and path between mental health and burnout of Chinese athletes - Gao, Yun; Wang, Lei (Frontiers in Psychology, 2024)
This study aims to explore the relationship and influencing pathways between mental health indicators and athlete burnout among Chinese competitive athletes. A cross-sectional study was conducted on 501 elite Chinese athletes from several national and provincial sports teams. Generalized Anxiety Disorder Scale (GAD-7) was used to measure anxiety, Patient Health Questionnaire (PHQ-9) was used to measure depression, Athlete Psychological Strain Questionnaire (APSQ) was used to measure perceived stress, and Athlete Burnout Questionnaire (ABQ) was used to measure burnout. The results were derived using reliability testing, descriptive statistics, correlation analyses, and structural equation modeling. the following results were obtained: (a) the clinical detection rates of anxiety and depression in this sample were within normal levels, but the detection rate of perceived stress (78.64%) was relatively high; (b) all three mental health indicators were significantly correlated with athlete burnout; (c) in our model, there was a direct path with APSQ directly contributing to 69.95% of the variance in athlete burnout, and two indirect paths with APSQ exerting an indirect effect through depression or/and anxiety accounting for 30.05% of the variance. The findings revealed the psychological characteristics of Chinese competitive athletes and the direct and indirect effects of the APSQ on burnout. Future research should actively promote the international development and application of burnout assessment tools, conduct more comprehensive studies on athlete mental health monitoring, and intensify efforts in athlete education, treatment, and support services, as well as strategies for athlete's coping stress.